1960
DOI: 10.1042/bj0740398
|View full text |Cite
|
Sign up to set email alerts
|

Specific lipopolysaccharides of Bordetella

Abstract: In nmany species of Granm-negative bacteria one of the surface components of the bacterial cell is a material composed of polysaccharide, protein and phospholipid residues (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1962
1962
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Isolation of lipopolysaccharide ( LPS) LPS was extracted from the two strains by Westphal's hot phenol-water method according to MacLennan (10), and treated further with DNase, RNase, and trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of lipopolysaccharide ( LPS) LPS was extracted from the two strains by Westphal's hot phenol-water method according to MacLennan (10), and treated further with DNase, RNase, and trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Serum antibodies to B. bronchiseptica were detected by an indirect haemagglutination test using goose erythrocytes sensitized with specific B. bronchiseptica lipopolysaccharide (MacLennan, 1960).…”
Section: Serologymentioning
confidence: 99%
“…It has been noted by MacLennan [5] that endotoxins isolated from members of the genus Bordetella are unusually resistant to acid-catalysed hydrolysis. This has been confirmed both in the previous [7] and the present study, treatment with quite strong acid being required (4 M HC1, 100 "C, 2 h) to release the uronic acid present.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been established that uronic acids are integral parts of the endotoxins of some gramnegative bacteria which do not belong to the family Enterobucteriuceae. Thus Volk [4] demonstrated that D-galacturonic acid was present in the endotoxin of 17 different species of Xunthomonus (Pseudomonuduceue) and MacLennan observed [5] that during acidic hydrolysis of the endotoxin extracted from Bordetellu bronchiseptica (Brucelluceue) carbon dioxide was released in amounts indicating the presence of about 20% of uronic acid in that lipopolysaccharide. It was, however, stressed by MacLennan that the presence of uronic acids could not be demonstrated either by paper chromatography of the hydrolysate or by colorimetric methods.…”
mentioning
confidence: 99%